2019
DOI: 10.3389/fimmu.2019.00919
|View full text |Cite
|
Sign up to set email alerts
|

Diet Rich in Animal Protein Promotes Pro-inflammatory Macrophage Response and Exacerbates Colitis in Mice

Abstract: Diet is a major factor determining gut microbiota composition and perturbances in this complex ecosystem are associated with the inflammatory bowel disease (IBD). Here, we used gnotobiotic approach to analyze, how interaction between diet rich in proteins and gut microbiota influences the sensitivity to intestinal inflammation in murine model of ulcerative colitis. We found that diet rich in animal protein (aHPD) exacerbates acute dextran sulfate sodium (DSS)-induced colitis while diet rich in plant protein (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 76 publications
4
59
0
Order By: Relevance
“…If the subjects consume the same diet, designed by a nutritionist or dietarian with standard formula, the result will be more promising and innovative. Some studies have reported that specific kinds of dietary fiber intake can lead to various results [ 29 , 30 ]. Athletes in groups who share diet and exercise patterns can lead to advanced results on the correlation between exercise and gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…If the subjects consume the same diet, designed by a nutritionist or dietarian with standard formula, the result will be more promising and innovative. Some studies have reported that specific kinds of dietary fiber intake can lead to various results [ 29 , 30 ]. Athletes in groups who share diet and exercise patterns can lead to advanced results on the correlation between exercise and gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between protein intake and gut microbiota composition has been investigated in several animal studies, giving conflicting results [78][79][80][81][82][83][84][85]. Rats fed a high-protein diet exhibited pro-inflammatory changes in gut microbiota composition, with an overrepresentation of pathobionts, such as Escherichia/Shigella and Enterococcus, depletion of species associated with the synthesis of short-chain fatty acids (SCFAs), such as Faecalibacterium, and protection of mucosa, such as Akkermansia [78,79]. These alterations of gut microbiota composition were emphasized when proteins were of animal origin [80].…”
Section: Animal Proteins and Microbiotamentioning
confidence: 99%
“…These include members of the Cystobasidiomycetes class (with emphasis on the species Cystobasidium sloofiae) and representatives [wuc] of the Sporidiobolaceae family. Although there are few reports regarding the involvement of these fungal groups with diseaseassociated dysbioses, increased populations of Sporidiobolaceae have been detected in cervical mucosa lesions from HPV-infected women at low risk of malignancy (106), as well as in the intestine of mice submitted to diets rich in animal proteins (107). Moreover, the relative abundance of Cystobasidiomycetes was positively correlated with adiposity, while negatively correlated with the serum concentration of LDL cholesterol in obese and lean subjects (69).…”
Section: Discussionmentioning
confidence: 99%